Correlation between histomorphometric changes and the type of aerobic bacteria isolated in chronic suppurative otitis media - Živković-Marinkov Emilija; Stanković Milan; Mihailović Dragan; Bojanović Mila (Vojnosanitetski Pregled)
Background/Aim. Bacterial flora is a very important factor in pathogenesis of chronic suppurative otitis media (CSOM) and significantly influences the type and intensity of osteolytic process. There are few histomorphometric investigations of middle ear mucosa in chronic otitis. The aim of this study was to identify aerobic bacteria responsible for chronic suppurative otitis media as well as their association with histomorphometric changes of middle ear mucosa. Methods. A prospective study that comprised 153 patients treated in the Clinc for Ear, Thorat and Nose Diseases, Niš, was conducted. Bacteriologic analysis of diseased ear secretion was carried out in all patients. Intraoperatively removed granulation tissue was used for histomorphometry. The analysed parameters were: the number of inflammatory cells, as well as vascularization and vasodilatation. Results. The most frequently isolated aerobic bacteria from chronic suppurative otitis media were Staphylococcus aureus (29.02%), Pseudomonas aeruginosa (29.02%) and Proteus spp. (21.76%). There was no correlation between the type of pathologic process and the type of bacteria.The number of inflammatory cells in the granulation tissue in pure cultures of Staphylococcus aureus was 1,597.33 ± 549.45 and in Pseudomonas auriginosa cultures was 2,639 ± 648. Conclusion. This study showed that there is a statistically significant correlation between the number of inflammatory cells in the granulation tissue and the type of aerobic bacteria we isolated. The intensity of the infection in chronic suppurative otitis media depends on the type of the isolated bacteria, which emphasizes the importance of adequate preoperative antimicrobial therapy.